pH-Responsive Association Behavior of Biocompatible Random Copolymers Containing Pendent Phosphorylcholine and Fatty Acid - Yusa, Shin-Ichi (Langmuir : the ACS journal of surfaces and colloids, 2022)
Well-defined pH-responsive biocompatible random copolymers composed of 2-(methacryloyloxy)ethyl phosphorylcholine and varying quantities of sodium 11-(acrylamido)undecanoate (AaU) (fAaU = 0-58 mol %) were synthesized via reversible addition-fragmentation chain transfer radical polymerization. The pH-responsive association and dissociation behavior of the random copolymers was studied via turbidity, 1H nuclear magnetic resonance relaxation time, dynamic light scattering, static light scattering (SLS), and fluorescence measurements. At basic pH levels, the random copolymers dissolved in water in a unimer state because the AaU units behaved in a hydrophilic manner as a result of the ionization of the pendent fatty acids. The random copolymers with fAaU < 52 mol % associated intramolecularly within a single polymer chain to form unimer micelles at pH 3 because of the protonation of the pendent fatty acids. On the other hand, the random copolymer with fAaU ≥ 52 mol % formed intermolecular aggregates composed of four polymer chains at pH 3, as established by the SLS measurements. The random copolymers displayed the ability to solubilize hydrophobic guest molecules, such as N-phenyl-1-naphthylamine, into the hydrophobic microdomain formed by the pendent dehydrated fatty acids at acidic pHs. At pH 4, 1-pyrememethanol is captured by the random copolymer with fAaU = 52 mol %, and it is released from the random copolymer above pH 9. Furthermore, the mucoadhesive properties of the random copolymer with fAaU = 9 mol % were studied using a surface plasmon resonance technique. The copolymer was adsorbed onto mucin at pH 3; however, the adsorption decreased at pH 7.4